Heritopia World Heritage and modernity - Wienberg, Jes (Lund University Press, 2021)
Heritopia explores the multiple meanings of the past in the present, using the famous temples of Abu Simbel and other World Heritage sites as points of departure. It employs three perspectives in its attempt to understand and explain both past and present the truth of knowledge, the beauties of narrative, and ethical demands. Crisis theories are rejected as nostalgic expressions of contemporary social criticism. Modernity is viewed as a collection of contradictory narratives and reinterpreted as a combination of technological progress and recently evolved ideas. The book argues that while heritage is expanding, it is not to be found everywhere, and its expansion does not constitute a problem. It investigates the World Heritage Convention as an innovation, demonstrating that the definition of a World Heritage site succeeds in creating a tenable category of outstanding and exclusive heritage. The book introduces the term "Heritopia" in order to conceptualise the utopian expectations associated with World Heritage. Finally, it points to the possibilities of using the past creatively when meeting present-day and future challenges.